Modern Problems of Investment Cooperation Development in the Supply Chain of the World Economy - Galeeva, Gulnaz M.; Paiduganova, Inna V.; Zagladina, Elena N. (International Journal of Supply Chain Management, 2018)
This paper considers the problems and dynamics of investment cooperation development in the supply chain of the world economy. The following factors have been selected foridentification of current problems in the development of investment cooperation in the supply chain of world economy: distribution of investment flows by the developed countries, developing countries, economies in transition, and by regions of the world (Europe, North America, Africa, Asia, Latin America and Caribbean, Oceania). The study consists of several stages and is based on data published on the official websites of UNCTAD, BRICS, IMF and the World Bank. The study shows that the absolute leaders in terms of the attracted foreign direct investments for the years 2015-2016 remain the United States, the United Kingdom and Hong Kong. In the total volume of foreign direct investments inflow, the absolute advantage of 64% is in the services sector, the processing sector possesses 27%, and the extraction -7%. An important trend in the development of international investment cooperation has become the conclusion of international investment transactions (IIT) and regional agreements. Most of the countries, leading in FDI inflows are at the same time the leaders in terms of the number of concluded IITs.